2018
DOI: 10.1177/0306624x17751528
|View full text |Cite
|
Sign up to set email alerts
|

Self-Disclosure in Criminal Justice: What Form Does It Take and What Does It Achieve?

Abstract: Self-disclosure, the act of therapists revealing something about themselves in the context of a professional relationship, has been linked with higher levels of effectiveness when used by correctional workers. However, it is poorly defined in both criminal justice policy and criminological research which has resulted in a lack of understanding about the potential risks and benefits to practice and practitioners. This article uses literature from other fields (namely, social work, counselling, and psychotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…One participant made the point that many frontline workers have ‘lived experience’ even if they are not employed to provide support on that basis and might not publicly disclose that experience. This reflects others’ research that ‘lived experience’ is often not confined to ‘peer’ support workers and that experiential knowledge, albeit undisclosed and unacknowledged, informs many professionals’ practice (Phillips et al, 2018; Gray et al, 2017; Oates et al, 2017). This highlights how ‘expert knowledge’ lacks uniformity and those working in professional roles often possess a ‘hybrid identity’ which is central to their practice.…”
Section: The ‘Value’ Of Experiential Knowledgementioning
confidence: 56%
See 1 more Smart Citation
“…One participant made the point that many frontline workers have ‘lived experience’ even if they are not employed to provide support on that basis and might not publicly disclose that experience. This reflects others’ research that ‘lived experience’ is often not confined to ‘peer’ support workers and that experiential knowledge, albeit undisclosed and unacknowledged, informs many professionals’ practice (Phillips et al, 2018; Gray et al, 2017; Oates et al, 2017). This highlights how ‘expert knowledge’ lacks uniformity and those working in professional roles often possess a ‘hybrid identity’ which is central to their practice.…”
Section: The ‘Value’ Of Experiential Knowledgementioning
confidence: 56%
“…They're talking to someone who's been there (N6) Some however questioned pervasive assumptions about the inherent value of experiential knowledge and its status as a prior superior to professional knowledge or a pre-requisite for being a 'good' navigator. One participant pushed back on the value of self-disclosure for instance, describing instead an 'ex-smoker syndrome' whereby lived experience or inappropriate disclosure (Phillips et al, 2018) can generate negative effects (Corcoran and Grotz, 2015). She explained how she does not disclose her own past in recognition that her experience does not necessarily have relevance to another's journey.…”
Section: The 'Value' Of Experiential Knowledgementioning
confidence: 99%
“…The POs stated that a way to build a trusting relationship is to make use of self-disclosure. There are already several authors who suggest the importance of self-disclosure, Phillips et al (2018) has made an initial inventory and their study showed that this technique is regularly used to build a working alliance.…”
Section: Discussionmentioning
confidence: 99%
“…Some, however, questioned pervasive assumptions about the inherent value of experiential knowledge and its status as a priori superior to professional knowledge or a prerequisite for being a 'good' navigator. One participant pushed back on the value of selfdisclosure for instance, describing instead an 'ex-smoker syndrome' whereby lived experience or inappropriate disclosure can generate negative effects (Phillips et al, 2018).…”
Section: Sadie Parrmentioning
confidence: 99%